2020
DOI: 10.3390/polym12112509
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Functionalized Dibenzhydryl Substituents in α-Diimine Pd Catalyzed Ethylene Polymerization and Copolymerization

Abstract: Sterically bulky diarylmethyl-based ligands have received increasing attention in the field of late-transition-metal catalyzed olefin polymerization. Ortho-substituents may have a significant impact on the performance of diarylmethyl-based α-diimine Pd catalysts. In this contribution, a series of α-diimine Pd catalysts bearing ortho-methoxyl/hydroxyl functionalized dibenzhydryl units were prepared, characterized, and investigated in ethylene polymerization and copolymerization with methyl acrylate (MA). The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…[ 52 ] Interestingly, the nickel complexes bearing nitro substituents ( Ni NO , Ni ON , Ni HN , and Ni NN ) resulted in high catalytic activities and produced very high molecular weight polyethylene products (Table 1, entries 11—30), indicating the beneficial effects of the nitro group [ 46‐51 ] and the diarylmethyl moiety. [ 45,52‐54 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ] Interestingly, the nickel complexes bearing nitro substituents ( Ni NO , Ni ON , Ni HN , and Ni NN ) resulted in high catalytic activities and produced very high molecular weight polyethylene products (Table 1, entries 11—30), indicating the beneficial effects of the nitro group [ 46‐51 ] and the diarylmethyl moiety. [ 45,52‐54 ]…”
Section: Resultsmentioning
confidence: 99%
“…Imine based late‐transition metal catalysts have a distinctive status in ethylene home and co‐polymerization 1–3 . A range of ligands such as, α ‐diimine, 4–10 salicylaldimines, 11–18 imino‐pyridyl, 19–25 keto‐imine, 26,27 iminopyridine‐ N ‐oxide, 28,29 pyrrole‐imines 30 and pyrazolyl‐imines 31–33 have been synthesized by simple condensation method. A literature survey revealed that, any structural modification either in the amines or carbonyl containing backbone has characteristic influence not only on the catalyst performance but also on the polymer properties such as, molecular weight and microstructure 34–43 .…”
Section: Introductionmentioning
confidence: 99%
“…Palladium has been long considered as the most suitable element for ethylene copolymerization with polar comonomers. Its importance was recognized after the remarkable incorporation of methyl acrylate into the polyolefin backbone using Brookhart-type α-diimine catalysts. , Despite the leading status of palladium, nickel also plays an influential role in this race. Recently, both industrial and academic researchers have commenced to appreciate the elusive differences and benefits that nickel can offer compared to palladium due to its low cost and the capability to produce polymers with high molecular weight. In this scenario, a range of ligands have been explored such as N^N-type, N^O-type, and P^O-type ligands.…”
Section: Introductionmentioning
confidence: 99%